ASSESSMENT OF SCARCITY OF WOODWORK ARTISAN IN BUILDING CONSTRUCTION IN KWARA STATE, NIGERIA - B, Kareem W; O, Okwori R; I, Issa A; O, Mrs. Abubakar H (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2018)
Woodwork artisanal scarcity is at an alarming rate in Nigeria and in Kwara state in particular. The reason being that most of the available woodwork artisans lack adequate skills demanded quality Building Construction. Generally, the issue of woodwork artisanal scarcity is not a current one as it dates as far back as the two World Wars. This study is on the causes of the observed scarcity of woodwork artisans in Nigeria and Kwara state in particular. The objectives of the study were to identify the factors increasing woodwork artisanal scarcity in Kwara state, its effect on Kwara state economy and the possible remedies. The study employed the use of descriptive survey design which involves the use of a structured questionnaire to collect data from 25 contractors and 35 woodwork artisans in carpentry and joinery. There was no sampling because the population is manageable, hence, the entire population was used. Mean ratings were used to answer research questions. The findings show that major factors causing the scarcity of woodwork artisans include; fluctuating payment, low remuneration, low motivation, lack of interest to take-up woodwork trade by youth, technological advancements in tools, equipment and working process. It also identified the effects of scarcity of woodwork artisan on Kwara state economy. Based on the finding of the study, it was recommended that the Carpentry and Joinery Union of Kwara state should encourage the welfare of its members in order to improve the issues raised by this study.